2013
DOI: 10.1111/cen.12183
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin in obese children: a bridge between inflammation and metabolic‐endocrine dysfunction

Abstract: Prolactin represents a prognostic marker for obese children and a predictive factor for progression to MS. PRL measurement may be useful as part of the endocrine work-up of obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 34 publications
6
52
1
3
Order By: Relevance
“…A small nonrandomized clinical study found that HDL cholesterol was not lower in 15 hyperprolactinemic patients compared with controls, and HDL cholesterol did not change significantly after treatment with cabergoline 21. In contrast to our findings, a pediatric study reported a positive association between baseline prolactin and HDL cholesterol at 1‐year follow‐up 22. Our longer study duration, different patient population, and evaluation of prolactin within the normal range may partially account for our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…A small nonrandomized clinical study found that HDL cholesterol was not lower in 15 hyperprolactinemic patients compared with controls, and HDL cholesterol did not change significantly after treatment with cabergoline 21. In contrast to our findings, a pediatric study reported a positive association between baseline prolactin and HDL cholesterol at 1‐year follow‐up 22. Our longer study duration, different patient population, and evaluation of prolactin within the normal range may partially account for our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…The same study revealed that prolactin release by subcutaneous adiposity was inversely correlated with BMI [8]. These data provided an explanation for the studies reporting a decreased prolactin level in obese subjects, compared with lean subjects [2]. However, it is possible that the predominance of visceral adiposity modified this relationship, as suggested by Kok et al, who showed that premenopausal women with visceral obesity had higher basal and pulsatile secretion of prolactin, compared with lean controls [27].…”
Section: Discussionmentioning
confidence: 70%
“…The inverse associations between serum prolactin level and adipose tissue quantity markers observed in our study suggested that the prolactin produced by adipocytes contributed significantly to the circulating prolactin. Clinical studies regarding the relationship between serum prolactin level and adiposity have reported both a positive [25] and a negative relationship [2] or no relationships at all [26], probably reflecting the numerous factors modulating the connection between the two parameters. One of these factors could be the type of adiposity, as suggested by Hugo et al [8], who reported decreased prolactin secretion by the subcutaneous adipose tissue compared with the visceral adipose tissue in obese patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations